Ondulierstab OS 76, Plattenspieler Türkis 524, Coctailstuhl Monice, Wofalor - Markennamen im Wortschatz der deutschen Sprache - Pohl, Inge (Studia Germanica Posnaniensia, 2018)
The article is an attempt to show the tendencies in the naming of goods in the former East German industry. Seven patterns of trade-names are presented and several pragmatic and stylistic aspects of the respective information are taken into account, such as the interest of the producer and the consumer, the use of metaphor and metonymy, colloquial elements and proper nouns.